Incidence of respiratory tract infections and antibiotic use in primary health care - Pietrzykowska, Małgorzata; Nowicka-Sauer, Katarzyna; Gutknecht, Piotr; Siebert, Janusz (Family Medicine & Primary Care Review, 2016)
Background . Respiratory tract infections are of viral etiology in around 70% of cases. The most popular treatment method is the empirical approach based on a medical interview and a physical examination, using the doctor’s personal experience. Contrary to ecommendations, antibiotic overuse is prevalent. The excessive use of antibiotics is a major factor contributing to the growing antibiotic resistance of bacteria, leading to epidemiological risk. Objectives. This study aimed to establish the incidence of respiratory tract infection and analyze the structure of antibiotic prescription in primary health care (PHC ). Material and methods. Retrospective medical records of 500 adult patients treated for respiratory tract infection in the first quarter of 2014, in a PHC facility in Pomeranian province were examined. The age median was 51 (range: 18 to 100). The study was focused on the incidence of disease diagnosis as classified by IC D-10 and on the treatment method used with respect to various antibiotic groups. Results . Acute upper respiratory tract infection with multiple or unspecified sites was diagnosed in 286 (57.2%) patients. Acute bronchitis was the second most common diagnosis (10.2%). Two patients were diagnosed with influenza (0.4%). As many as 67.2% of all patients were treated with antibiotics. Semisynthetic penicillin – such as amoxicillin or amoxicillin with clavulanic acid – (46.43% in total) and macrolides (36.31%) were the most frequently prescribed. Conclusions . 1. Acute upper respiratory tract infection with multiple or unspecified sites was diagnosed most frequently. 2. Despite increasing awareness of the risks associated with the excessive use of antibiotics, antimicrobials were often prescribed. Semisynthetic penicillins and macrolides were used most often. 3. Implementation of uniform national standards for the diagnosis and treatment of respiratory tract infections is essential. 4. Systematic training in effective and judicious use of antimicrobial therapy seems necessary for every physician.